Menciptakan Desain Interior Perpustakaan Ramah Anak di Sekolah Dasar Negeri Potrobangsan 1 Kota Magelang: Best Practice (Creating Interior Design for Child-Friendly Library in Primary School of Potrobangsan 1, Magelang City: Best Practice) - Dicki Agus Nugroho; Sri Haryati (Jurnal Pustakawan Indonesia, 2018)
School librarian must deliver information literacy for students in library. Than librarian create comfortable interior design, so student will enjoy library, and librarian can teach students easily. One of the best interior design of Child-Friendly Library is Room To Read method. The writer has been involved in this program, use best practice method in this research, so this research explain how to creating interior design of Child-Friendly Library in primary school. The result of this research are two steps to change library is like library as Room To Read’s design interior. The steps are (1) must have a room and (2) comfortable, safe, & secure interior design. The writer uses colorful pieces of paper to reset the furniture, so it is easy to apply. Keywords: mentoring, interior design, child-friendly library, school library, room to read,